2021
DOI: 10.2147/rmhp.s277135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Urology Practice in Saudi Arabia

Abstract: From the moment the World Health Organization (WHO) declared COVID-19 to be a pandemic disease, COVID-19 began to affect the lives of many healthcare providers worldwide. In response to this pandemic, urology departments and training residency programs implemented urgent measures to reduce outpatient clinics, adopted the use of telemedicine, regulated emergency and outpatient urological procedures, promoted the use of operating theatres, and developed the use of sustainable e-learning alternatives to tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…This finding is consistent with the recommendations of international organizations and the measures adopted to mitigate the negative impacts of the COVID-19 epidemic [ 19 21 ]. Most Saudi governmental hospitals applied these measures [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the recommendations of international organizations and the measures adopted to mitigate the negative impacts of the COVID-19 epidemic [ 19 21 ]. Most Saudi governmental hospitals applied these measures [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our respondents reported modest levels of stress related to sexuality and partner relationships, indicating that their sexual connections were not jeopardized during the lockdown. This could be owing to the Saudi government’s early implementation of specific preventative measures and heightened public knowledge about the pandemic, which appeared to have a protective effect on people’s overall health [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our hospital is one of the most important health care facilities in Riyadh, serving as referral center for about one million populations. The impact of COVID-19 has been previously reported in Saudi Arabia, while some of these studies[ 13 14 15 ] have reported a generalized overview of the adaptive functioning in the context of COVID-19 in respective specialties, one study has reported impact on services. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, studies have been conducted on the impact of COVID-19 across the specialties;[ 10 12 13 14 15 ] however, not much has been studied on the surgical volume affected overall in a secondary care hospital, which prompted us to undertake this study. The present study had been taken up in King Salman Hospital in First central health cluster, Ministry of Health, Riyadh, Saudi Arabia, with following objectives: To assess the effect of COVID-19 on OR utilization during the pre-COVID-19 and COVID-19 phase.…”
Section: Introduction/backgroundmentioning
confidence: 99%